Relationship of Self-esteem with Depression, Anxiety and Stress among Pakistani medical students - Rizwan, Hufsa Chandni; Rahman, Saeed ur; Habib, Osama; Khan, Muhammad Ashar Waheed; Malik, Saad Bashir; Minhas, Iftikhar Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Previous research on self-esteem highlights that low self-esteem is related to higher levels of anxiety, depression and stress. However, this relationship has not been clearly demonstrated in Pakistani adolescents and young adults. Aim: To explore the relationship between self-esteem and the prevalence of anxiety, depression and stress in Pakistani medical students. Methods: The study was conducted at Shalamar medical and dental college (SMDC) from August to September 2016. 273 students participated in this study which was approved the ethical review board at SMDC. Depression, anxiety and stress scale (DASS) was used to asses stress, anxiety and depression and Rosenberg self-esteem scale (RSES) was used to assess self-esteem. Results: A significant inverse relationship was found between self-esteem and the prevalence of anxiety depression and stress i.e. higher levels of self-esteem tended to correlate significantly with lower prevalence of anxiety, depression and stress in our study population. Conclusions: It is important to assess self-esteem among individuals who present with symptoms of anxiety and depression. Training on how to boost one’s self-esteem can be one of the strategies used to treat and prevent depression and anxiety, especially among students and young adults.